KHAP: Using Keyed Hard AI Problems to Secure Human Interfaces - King, Jeff; Santos, Andre dos; Xuan, Chaoting (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2004: Anais do IV Workshop em Segurança de Sistemas Computacionais, 2004)
There is often a need for users to securely interact with a remote computing system. Typical solutions assume that a local trusted computing platform is available, but this is often not the case. We introduce KHAP, a protocol for using hard artificial intelligence problems to provide message authentication checks centered around a human verifier. We also formally introduce the notion of a keyed hard AI problem, which is one that uses an authentication key to prove the source and integrity of a message. We give examples of some keyed hard AI problems, as well as examples of KHAP’s applicability to the specific problem domains of Internet voting and the use of smartcards for digital signatures.